The proposed alignment framework in enterprise architecture development for the Omani public sector - Al Kharusi, Hamood (2018)
The misalignment between Enterprise Architecture (EA) development and stakeholders’ goals plays a vital role in the low acceptance of EA in organizations and governments. Literature has highlighted the need for an alignment framework to support enterprise architects to align the development process of EA with the stakeholders’ goals. Hence, this research developed an alignment framework to align the EA development process with the stakeholders to produce an agreed architecture that supports the architects. Multiple Perspectives Theory (MPT) was used to develop a preliminary research model that provided the initial guidance in data collection and analysis. The research employed a qualitative case study approach to build an in-depth understanding of EA development process, enterprise architects and stakeholders’ roles, as well as the factors influencing the alignment between them. The Government Architecture Framework (GAF) of the Omani public sector was used as the case study that included GAF documentation review, and interviews with architects and stakeholders who participated in the development of GAF. The findings showed that twelve alignment factors influenced the development of GAF which are standardization, development scope, principles, governance, top management support, culture, commitment, awareness, communication, value of EA, change management capability and experience. These factors were used as the base to develop the alignment framework followed by a focus group session with GAF architects was organized to validate the final framework. As a conclusion, the study has shown that the alignment framework provides a comprehensive understanding for practitioners and academicians about the factors and their influences at each EA development step.